2021
DOI: 10.1016/j.jbc.2021.100774
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental factors regulate the type 1 diabetes gene CTSH via differential DNA methylation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Such a process is likely to cause injury to b cells, ultimately contributing to the development of T1D. Another study observed that the incidence of T1D was found to correlate with high CTSH expression, which itself is modified by other environmental factors such as epigenetics and post-translational modifications (42). Taken together, these studies highlight the role of CTSH in increased susceptibility of developing T1D.…”
Section: Cathepsin Hmentioning
confidence: 85%
“…Such a process is likely to cause injury to b cells, ultimately contributing to the development of T1D. Another study observed that the incidence of T1D was found to correlate with high CTSH expression, which itself is modified by other environmental factors such as epigenetics and post-translational modifications (42). Taken together, these studies highlight the role of CTSH in increased susceptibility of developing T1D.…”
Section: Cathepsin Hmentioning
confidence: 85%
“…Recent evidence suggests that not only genetic but also environmental influences on T1D genetic loci are mediated by differential levels or patterns of DNA methylation (hypo or hypermethylation) [8,45,46]. For example, some of the genes that have been identified to be associated with T1D, such as GAD2 and HLA-DQB1, were found to be hypomethylated or hypermethylated [7].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, individuals who carry the T1D risk variant exhibited less variability in methylation at the CpG residues in intron 1, presumably making them less responsive to cytokines. On the other hand, individuals who carry the protective variant demonstrated greater methylation variability, presumably increasing their sensitivity to cytokines, suggesting that the two populations may respond differently to environmental factors [45].…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that non-twin studies using T1D patients and healthy individuals have demonstrated differences in methylation profiles between T1D patients and controls [141,151]. Indeed, recent research has shown that DNA methylation is involved in regulating the genetic and environmental influence of T1D at the CTSH locus [149].…”
Section: Dna Methylation Signature In T1dmentioning
confidence: 99%